Biomarkers of environmental enteropathy, inflammation, stunting, and impaired growth in children in Northeast Brazil - Guerrant,RL; Leite,AM; Pinkerton,R; Medeiros,PHQS; Cavalcante,PA; DeBoer,M; Kosek,M; Duggan,C; Gewirtz,A; Kagan,JC; Gauthier,AE; Swann,JR; et al. (PLOS One, 2016)
Critical to the design and assessment of interventions for enteropathy and itsdevelopmental consequences in children living in impoverished conditions arenon-invasive biomarkers that can detect intestinal damage and predict its effectson growth and development. We therefore assessed fecal, urinary and systemicbiomarkers of enteropathy and growth predictors in 375 6-26 month-old childrenwith varying degrees of malnutrition (stunting or wasting) in Northeast Brazil. 301of these children returned for followup anthropometry after 2-6m. Biomarkersthat correlated with stunting included plasma IgA anti-LPS and anti-FliC, zonulin(if >12m old), and intestinal FABP (I-FABP, suggesting prior barrier disruption);and with citrulline, tryptophan and with lower serum amyloid A (SAA) (suggestingimpaired defenses). In contrast, subsequent growth was predicted in those withhigher fecal MPO or A1AT and also by higher L/M, plasma LPS, I-FABP andSAA (showing intestinal barrier disruption and inflammation). Better growth waspredicted in girls with higher plasma citrulline and in boys with higher plasma tryptophan. Interactions were also seen with fecal MPO and neopterin inpredicting subsequent growth impairment.Biomarkers clustered into markers of 1) functional intestinal barrier disruption andtranslocation, 2) structural intestinal barrier disruption and inflammation and 3)systemic inflammation. Principle components pathway analyses also showedthat L/M with %L, I-FABP and MPO associate with impaired growth, while also(like MPO) associating with a systemic inflammation cluster of kynurenine, LBP,sCD14, SAA and K/T. Systemic evidence of LPS translocation associated withstunting, while markers of barrier disruption or repair (A1AT and Reg1 with lowzonulin) associated with fecal MPO and neopterin.We conclude that key noninvasive biomarkers of intestinal barrier disruption, LPStranslocation and of intestinal and systemic inflammation can help elucidate howwe recognize, understand, and ass